A review on microencapsulation in improving probiotic stability for beverages application / Safiah Sabrina Hassan … [et al.] - Hassan, Safiah Sabrina; Ahmad Fadzil, Intan Nabihah; Yusoff, Anida; Abdul Khalil, Khalilah (Faculty of Applied Sciences, 2020)
Nowadays, probiotic bacteria are extensively used in beverages application to deliver beneficial health effect to the consumer upon ingestion. Different entrapment techniques can be used to maintain the viability of probiotic bacteria during processing as well as during storage of beverage products. Development of artificial microcapsules from entrapment techniques are to support the growth and to provide protection on probiotic cells from unfavorable external conditions that may affect the viability of probiotics in beverages. Techniques that usually applied for probiotic entrapment in beverages are microencapsulation, emulsification, spray drying and extrusion. Biomaterials such as alginate, carrageenan, whey protein, gelatin, chitosan and starch are the most commonly used matrix in entrapment of lactic acid bacteria. Entrapment of probiotic is applied on beverages products such as fruit juice, yoghurt and ice cream.